Upregulation of an IAA-Glucosyltransferase OsIAGLU in Rice (Oryza sativa L.) Impairs Root Gravitropism by Disrupting Starch Granule Homeostasis - Guo Chen; Xiaoyu Fu; Xinya Ruan; Xiaolu Yu; Dianyun Hou; Huawei Xu (Plants)
Indole-3-acetic acid (IAA) glycosyltransferase (IAGLU) plays vital roles in modulating plant development and responses to environmental cues. Here, we elucidate the regulatory mechanism of OsIAGLU in modulating root gravitropism using OsIAGLU-overexpressing (OE) rice (Oryza sativa L.). OsIAGLU upregulation substantially decreases IAA levels, resulting in the impairment of multiple agronomic traits and root gravitropism, as well as nearly complete suppression of starch granule accumulation in rice root tips. Exogenous application of the auxin analog 1-naphthaleneacetic acid (NAA) effectively rescued both starch granule accumulation and root gravitropism. Starch synthesis genes exhibited relatively stable or slightly decreased expression following NAA treatments, whereas all starch degradation genes displayed a consistent downward trend in expression after NAA treatment. This suggests that starch degradation genes may play a more prominent role in regulating starch granule accumulation in rice roots, contrasting sharply with their roles in Arabidopsis. Moreover, decreased auxin levels perturbed the accumulation and distribution of hydrogen peroxide (H2O2) in rice root tips, while NAA treatment restored normal H2O2 distribution and accumulation in OE roots. This study clearly demonstrates that auxin not only functions in regulating agronomic traits but also plays an essential role in gravity perception by modulating starch granule accumulation in rice root tips.